Anda di halaman 1dari 4

Joenahhas1958@yahoomail.

com

You have to ask yourself the question Alfred: Do I feel Lucky? Do ya Alfred?
Alfred Nobel is not needed and not wanted
1 - Maximum energy E = mc2/2 by definition of energy
2 - Plank visually doubled E = mc2/2 to make up
Quantum Energy E = 2[ħ ν/2] = ħ ν
Quantum mechanics is not needed and not wanted
3 - Einstein visually doubled E = mc2/2 to make up
Relativistic Energy E = 2[mc2/2] = mc2
Relativistic mechanics is not needed and not wanted

All there is in the Universe is objects of mass m moving in space (x, y, z) at a

location r = r (x, y, z). The state of any object in the Universe can be expressed
as the product
S = m r; State = mass x location:
P = d S/d t = m (d r/d t) + (dm/d t) r = Total moment
= change of location + change of mass
= m v + m' r; v = velocity = d r/d t; m' = mass change rate
F = d P/d t = d²S/dt² = Total force
= m (d²r/dt²) +2(dm/d t) (d r/d t) + (d²m/dt²) r
= m γ + 2m'v +m" r; γ = acceleration; m'' = mass acceleration rate
In polar coordinates system
r = r r (1) ;v = r' r(1) + r θ' θ(1) ; γ = (r" - rθ'²)r(1) + (2r'θ' + r θ")θ(1)
r = location; v = velocity; γ = acceleration

Page 1
F = m γ + 2m'v +m" r
F = m [(r"-rθ'²) r (1) + (2r'θ' + r θ") θ (1)]
+ 2m'[r' r (1) + r θ' θ (1)] + (m" r) r (1)
= [d² (m r)/dt² - (m r) θ'²] r (1) + (1/mr) [d (m²r²θ')/d t] θ (1)
= 0 Light force law

Proof:
First r = r [cosine θ î + sine θ Ĵ] = r r (1)
Define r (1) = cosine θ î + sine θ Ĵ

Define v = d r/d t = r' r (1) + r d[r (1)]/d t

= r' r (1) + r θ'[- sine θ î + cosine θĴ]
= r' r (1) + r θ' θ (1)

Define θ (1) = -sine θ î +cosine θ Ĵ;

And with r (1) = cosine θ î + sine θ Ĵ
Then d [θ (1)]/d t= θ' [- cosine θ î - sine θ Ĵ= - θ' r (1)
And d [r (1)]/d t = θ' [-sine θ î + cosine θ Ĵ] = θ' θ (1)

Define γ = d [r' r (1) + r θ' θ (1)] /d t

= r" r (1) + r'd [r (1)]/d t + r' θ' r (1) + r θ" r (1) +r θ'd [θ (1)]/d t
γ = (r" - rθ'²) r (1) + (2r'θ' + r θ") θ (1)

With d² (m r)/dt² - (m r) θ'² = F (r)

And d (m²r²θ')/d t = 0

If mass m = constant, then

With d² r/dt² - r θ'² = F (r) Eq-1
And d (r²θ')/d t = 0 Eq-2

With d² r/dt² - r θ'² = 0 Eq–1

And d (r²θ')/d t = 0 Eq-2

From Eq-2: d (r²θ')/d t = 0

Then r²θ' = h = constant

Differentiate with respect to time

Then 2rr'θ' + r²θ" = 0
Page 2
Divide by r²θ'
Then 2(r'/r) + θ"/θ' = 0
And 2(r'/r) = - θ"/θ' = 2(λ + ỉ ω)

Also, r = r0 (θ, 0) e (λ + ỉ ω) t
And θ' = θ' 0 (θ, 0) e -2(λ + ỉ ω) t

For a fixed orbit: λ = 0

Also, r = r 0 (θ, 0) e ỉ ω t
And θ' = θ' 0 (θ, 0) e -2ỉ ω t

With d² r/dt² - r θ'² = 0

Let u = 1/r; r = 1/u; r²θ' = h = θ’ /u²

And d r/d t = (d r/ d u) (d u /d θ) (d θ/ d t)
= (- 1/u ²) (θ’) (d u/ d θ)
= - h (d u/ d θ)

And d² r/ d t² = - h (θ’) (d² u/ d θ ²)

= [- h²/r²] (d² u/ d θ ²)
= - h² u² (d² u/ d θ ²)

And - h² u² (d² u/ d θ ²) – (1/u) (h u²) ² = 0

Then (d² u/ d θ ²) + u = 0

Then u = A e - í θ
Then r 0 (θ, 0) = (1/A) e í θ
And r 0 (θ, 0) = r 0 (0, 0) e í θ

íθ ỉωt
And r = r 0 (0, 0) e e
í (θ + ω t)
Or, r = r 0 e

- í 2 (θ + ω t)
And θ' = θ'0 e

Page 3
í (θ + ω t)
And wave equation velocity v= [v 0 + í (θ' + ω)] r 0 e
Energy E = m v2/2

í 2 (θ + ω t)
E = (m/2) [v 0 + í (θ' + ω)] 2
e
- í 2 (θ + ω t) í 2 (θ + ω t)
E = (m/2) [v 0 + í (θ'0 e + ω)] 2
r2 0 e

- í 2 (θ + ω t) í 2 (θ + ω t)
E = (m/2) [v 0 + í (θ'0 e + ω)] 2
r2 0 e

Let v 0 = 0, θ = 0

-í2ωt í2ωt
Then E = (m/2) í2 (θ'0 e + ω) 2
r2 0 e

-í2ωt í2ωt
E = - (m r2 0/2) (θ'0 e + ω) 2
e
-í4ωt -í2ωt í2ωt
E = - (m r2 0/2) [θ'02 e + 2 ω θ'0 e +ω2] e

-í2ωt í2ωt
E = - (m r2 0/2) [θ'02 e + 2 ω θ'0 + ω2 e ]

Ex = - (m r2 0/2) (2 ω θ'0) = - (m r2 0 θ'0/2) (2 ω)

= - 2 h0 ω; h0 = m r2 0 θ'0

Ex = - h ω = - (h/2 π) (2 π ω) = - ħ ν; θ'0 = ω